2019
DOI: 10.1002/jac5.1166
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacists' perceptions and practice changes resulting from emergence of the vancomycin‐piperacillin/tazobactam nephrotoxicity phenomenon

Abstract: Purpose To elucidate the considerations pharmacists have when using concomitant vancomycin and piperacillin/tazobactam (VPT) and strategies implemented across hospitals in response to published data on this phenomenon. Methods A survey of pharmacist members of the infectious diseases and critical care (CC) practice and research networks of the American College of Clinical Pharmacy was conducted. Participants were grouped based on their belief (yes or no) in the association between VPT and acute kidney injury (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Importantly, the number of studies published on the potential nephrotoxicity of vancomycin and piperacillin-tazobactam have influenced prescribing patterns, which may have downstream implications. In a survey of infectious disease and critical care pharmacists, 89% of respondents reported a belief that the combination of vancomycin and piperacillin-tazobactam resulted in an increased probability of developing AKI compared with vancomycin alone or in combination with other beta-lactam antibiotics (5). Of those respondents, 64% reported they less frequently recommend the combination of vancomycin and piperacillin-tazobactam in a patient with existing AKI (5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, the number of studies published on the potential nephrotoxicity of vancomycin and piperacillin-tazobactam have influenced prescribing patterns, which may have downstream implications. In a survey of infectious disease and critical care pharmacists, 89% of respondents reported a belief that the combination of vancomycin and piperacillin-tazobactam resulted in an increased probability of developing AKI compared with vancomycin alone or in combination with other beta-lactam antibiotics (5). Of those respondents, 64% reported they less frequently recommend the combination of vancomycin and piperacillin-tazobactam in a patient with existing AKI (5).…”
Section: Discussionmentioning
confidence: 99%
“…In a survey of infectious disease and critical care pharmacists, 89% of respondents reported a belief that the combination of vancomycin and piperacillin-tazobactam resulted in an increased probability of developing AKI compared with vancomycin alone or in combination with other beta-lactam antibiotics (5). Of those respondents, 64% reported they less frequently recommend the combination of vancomycin and piperacillin-tazobactam in a patient with existing AKI (5). This would appear to complicate the antibiotic selection for patients with sepsis and AKI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6] These data have seemingly altered prescribing practices in critically ill patients according to a recent survey that reported almost 90% of respondents affirmed a belief that the combination of VPT increases the risk of developing an AKI. 7 However, data supporting this relationship in strictly critically ill patient populations is more nuanced. Several studies have not demonstrated increased nephrotoxicity with VPT compared with vancomycin and other β-lactam combination therapies.…”
Section: Introductionmentioning
confidence: 99%
“…46 These data have seemingly altered prescribing practices in critically ill patients according to a recent survey that reported almost 90% of respondents affirmed a belief that the combination of VPT increases the risk of developing an AKI. 7…”
Section: Introductionmentioning
confidence: 99%